1994
DOI: 10.1016/s0006-3495(94)80775-1
|View full text |Cite
|
Sign up to set email alerts
|

MR diffusion tensor spectroscopy and imaging

Abstract: This paper describes a new NMR imaging modality--MR diffusion tensor imaging. It consists of estimating an effective diffusion tensor, Deff, within a voxel, and then displaying useful quantities derived from it. We show how the phenomenon of anisotropic diffusion of water (or metabolites) in anisotropic tissues, measured noninvasively by these NMR methods, is exploited to determine fiber tract orientation and mean particle displacements. Once Deff is estimated from a series of NMR pulsed-gradient, spin-echo ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
4,424
0
57

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,384 publications
(4,493 citation statements)
references
References 19 publications
12
4,424
0
57
Order By: Relevance
“…For comparison, we also fitted the standard diffusion tenor imaging (DTI) model31 to the measurements in Gaussian diffusion regime (up to b = 4680 sec mm −2 ) using in‐house Matlab code. From the fitted tensor, fractional anisotropy (FA), axial, radial, and mean diffusivities (AD, RD, and MD) were obtained in each MRI voxel.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, we also fitted the standard diffusion tenor imaging (DTI) model31 to the measurements in Gaussian diffusion regime (up to b = 4680 sec mm −2 ) using in‐house Matlab code. From the fitted tensor, fractional anisotropy (FA), axial, radial, and mean diffusivities (AD, RD, and MD) were obtained in each MRI voxel.…”
Section: Methodsmentioning
confidence: 99%
“…Past and current state of the art Diffusion-weighted magnetic resonance imaging (MRI), received strong attention for the first time in the early 90s as it proved to be a sensitive biomarker for acute stroke (Moseley et al, 1990). The second reason diffusion imaging came to attention, was because it was observed that not only does white matter exhibit reliable anisotropic properties (Basser et al, 1994;Douek et al, 1991) but that it is indeed possible to infer fiber tract trajectories on the basis of these patterns (Conturo et al, 1999;Mori et al, 1999;Wedeen, 1996). Diffusion Tensor Imaging and tractography was born.…”
Section: Mapping the Connectome With Mrimentioning
confidence: 99%
“…The b‐values specified included contributions from imaging and cross‐terms, and the diffusion gradient strength was adjusted accordingly 16. Diffusion tensor imaging (DTI) was performed with a 2D SE echo planar imaging sequence, and FA was measured in five central axial slices 17. Scan parameters were similar to the calibration scan with the following differences: number of non–diffusion‐weighted scans = 3, number of diffusion directions = 21 18, b‐value = 2000 s/mm 2 .…”
Section: Methodsmentioning
confidence: 99%